Determining the efficacy of ginger Zingiber officinale as a potential nutraceutical agent for boosting growth performance and health status of Labeo rohita reared in a semi-intensive culture system - Rawat, Priya; Kaur, Vaneet Inder; Tyagi, Anuj; Norouzitallab, Parisa; Baruah, Kartik (Frontiers in Physiology, 2022)
A 120-day feeding trial was conducted in a pilot field setting to study the nutraceutical properties of ginger powder (GP), focusing on the growth performance and health status of Indian major carp Labeo rohita reared under a semi-intensive culture system. L. rohita fingerlings were divided into five groups and fed a diet with no GP supplementation (control), or a diet supplemented with GP at 5 g (GP5), 10 g (GP10), 15 g (GP15), and 20 g (GP20) per kg of feed. The study was carried out in outdoor tanks (20 m2) following a complete randomized design with three replicates for each experimental group. Dietary supplementation of GP at 15 g kg-1 (GP15) of feed caused a significant increase in the growth performances of the fish. Results also showed that feeding of GP15 diet led to a significant improvement in the health status of fish as indicated by a marked change in the tested haematological indices (i.e., higher RBC, WBC, Hb, and Ht values), oxidative status (increased SOD and decreased LPO levels), biochemical parameters (increased HDL, decreased cholesterol and triglycerides levels), and activities of the liver enzymes (decreased AST and ALT). Overall results suggested that dietary supplementation of GP could positively influence the growth and health status of L. rohita fingerlings, and hence could be an important natural nutraceutical for sustainable farming of carp.